Tinjauan Literatur Tentang Pengembangan Gamifikasi untuk Meningkatkan Kemampuan Menulis Narasi Siswa Sekolah Dasar dalam Pembelajaran Bahasa Indonesia - Marshanda Aura Putri Sauri; Rena Ningsih; Ichsan Fauzi Rachman (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
Narrative writing skills are a crucial competency in Indonesian language learning at the elementary school level. However, many students still struggle to develop ideas, structure sentences, and use appropriate vocabulary. Innovation in learning is necessary to enhance student engagement in writing, one of which is the implementation of gamification. This study aims to explore how gamification can be used as an effective learning strategy to improve elementary school students’ narrative writing skills. The method used is a literature review with a descriptive qualitative approach, referring to relevant and credible literature from the past five years (2019–2024). The findings indicate that game elements such as points, challenges, rewards, and level systems in gamification can enhance students’ motivation, participation, and writing quality. Additionally, gamification supports the development of critical and collaborative thinking skills through interactive learning media such as Quizizz, Genially, and the Write Around model supported by digital picture series. However, challenges such as limited access to technology and the need for teacher training remain obstacles to its implementation. With careful planning and adequate infrastructure support, gamification has the potential to become an innovative solution in narrative writing instruction at the elementary school level.